Refining the Late Quaternary tephrochronology for southern South America using the Laguna Potrok Aike sedimentary record - Smith, R; Smith, V; Fontijn, K; Gebhardt, A; Wastegård, S; Zolitschka, B; Ohlendorf, C; Stern, C; Mayr, C (Elsevier, 2019)
This paper presents a detailed record of volcanism extending back to ∼80 kyr BP for southern South America using the sediments of Laguna Potrok Aike (ICDP expedition 5022; Potrok Aike Maar Lake Sediment Archive Drilling Project - PASADO). Our analysis of tephra includes the morphology of glass, the mineral componentry, the abundance of glass-shards, lithics and minerals, and the composition of glass-shards in relation to the stratigraphy. Firstly, a reference database of glass compositions of known eruptions in the region was created to enable robust tephra correlations. This includes data published elsewhere, in addition to new glass-shard analyses of proximal tephra deposits from Hudson (eruption units H1 and H2), Aguilera (A1), Reclus (R1, R2-3), Mt Burney (MB1, MB2, MBx, MB1910) and historical Lautaro/Viedma deposits. The analysis of the ninety-four tephra layers observed in the Laguna Potrok Aike sedimentary sequence reveals that twenty-five tephra deposits in the record are the result of primary fallout and are sourced from at least three different volcanoes in the Austral Andean Volcanic Zone (Mt Burney, Reclus, Lautaro/Viedma) and one in the southernmost Southern Volcanic Zone (Hudson). One new correlation to the widespread H1 eruption from Hudson volcano at 8.7 (8.6–9.0) cal ka BP during the Quaternary is identified. The identification of sixty-five discrete deposits that were predominantly volcanic ashes (glass and minerals) with subtle characteristics of reworking (in addition to three likely reworked tephra, and one unknown layer) indicates that care must be taken in the analysis of both visible and invisible tephra layers to decipher their emplacement mechanisms.